Problem Based Learning sebagai Strategi Penguatan Kemampuan Berpikir Kritis dalam Pembelajaran Ilmu Pengetahuan Sosial - Faisal Ahmad (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study aims to improve the critical thinking skills of fifth-grade students at SDN 020 Balung through the implementation of the Problem Based Learning (PBL) method. The research employed Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The subjects of the study were 32 students, with a focus on social studies learning. The research instruments included observation sheets, critical thinking skill tests, field notes, and interviews. Data were analyzed using a descriptive qualitative approach by comparing the results across cycles. The findings revealed a significant improvement in students’ critical thinking skills, particularly in identifying problems, providing logical reasons, asking questions, and drawing conclusions from discussions. The achievement level of critical thinking indicators reached 75–85% in the second cycle. Therefore, the implementation of PBL proved effective in enhancing elementary students’ critical thinking skills and provided practical implications for teachers in developing instructional strategies aligned with 21st-century curriculum demands. Additionally, PBL also increased students’ activeness, participation, and confidence in the learning process in the classroom